Análise Narrativa em Trabalhos de História da Educação Matemática: algumas considerações - Cury, Fernando Guedes [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Matemática, 2010)
This paper presents some reflections on the use of narrative analysis as a possible approach to study the History of (Mathematics) Education, mainly to interpret historical situations and biographical data. Its perspective is linked to Walter Benjamin's ideas about the figure of the narrator and how the dialogue between narrator and historian can be seen. Following the perspective of another author, Benedito Nunes, we try to establish relations among narratives, fiction and historiography, also highlighting the ideas of Jorge Larrosa regarding the transmission of experiences. Finally, our focus is turned to Antonio Bolivar and his alternative statements about why and how analysis of investigations, in which narratives are the main source of data, can be done.
Narrative Analysis in History of Mathematics Education Research: some considerations
Keywords: Narratives; Narrative Analysis; History; Mathematics Education